2022
DOI: 10.3389/fimmu.2022.1025681
|View full text |Cite
|
Sign up to set email alerts
|

STXBP3 and GOT2 predict immunological activity in acute allograft rejection

Abstract: BackgroundAcute allograft rejection (AR) following renal transplantation contributes to chronic rejection and allograft dysfunction. The current diagnosis of AR remains dependent on renal allograft biopsy which cannot immediately detect renal allograft injury in the presence of AR. In this study, sensitive biomarkers for AR diagnosis were investigated and developed to protect renal function.MethodsWe analyzed pre- and postoperative data from five databases combined with our own data to identify the key differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…In AD, both human and mouse studies using brain transcriptomic data also observed the prominent role of microglial and inflammatory mechanisms in sex differences in AD 31 , 32 . In agreement with these results, among the eight AD causal genes with either sex-biased expression or genetic regulation of protein expression that we identified, half of them are involved in immune function: CD2AP facilitates recognition of antigen by T cells 42 ; SLMAP participates in T cell receptor signaling 43 ; ADAM10 regulates cytokine levels in activated microglia 44 ; and STXBP3 is involved in immune function 45 , 46 .…”
Section: Discussionsupporting
confidence: 85%
“…In AD, both human and mouse studies using brain transcriptomic data also observed the prominent role of microglial and inflammatory mechanisms in sex differences in AD 31 , 32 . In agreement with these results, among the eight AD causal genes with either sex-biased expression or genetic regulation of protein expression that we identified, half of them are involved in immune function: CD2AP facilitates recognition of antigen by T cells 42 ; SLMAP participates in T cell receptor signaling 43 ; ADAM10 regulates cytokine levels in activated microglia 44 ; and STXBP3 is involved in immune function 45 , 46 .…”
Section: Discussionsupporting
confidence: 85%
“…Further correlational analyses between these five genes and 39 pathways unveiled distinct pathway signatures for protective and risk genes. Protective genes exhibited positive associations with pathways such as allograft rejection, myogenesis, complement, and interferon-gamma response, whereas risk genes were tied to fatty acid metabolism, xenobiotic metabolism, and adipogenesis [32,33]. Alterations in fatty acid metabolism have been implicated in GC pathogenesis, with demonstrated prognostic value of fatty acid metabolism-related genes [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“… 33 Circulating innate immune cells such as monocytes and dendritic cells have also been implicated in acute rejection, a key concern for kidney rejection, with genes such as aspartate aminotransferase demonstrating enriched expression in these cells. 34 Yet another process affecting kidney allograft and function is brain death associated inflammation; however, the pathophysiological process has been unclear. A recent report by Zitur et al 35 demonstrated an upregulation in circulating leukocytes and cytokines, activation of complement and coagulation pathways, and upregulation of genes associated with inflammation in both brain-dead and sham subjects relative to naive controls in a rhesus macaque disease model.…”
Section: Role Of Innate Immune Effector Cells Affecting Transplant Ou...mentioning
confidence: 99%